2018
DOI: 10.15252/emmm.201708349
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism promotes B‐cell positioning during immune pathogenesis of chronic obstructive pulmonary disease

Abstract: The development of chronic obstructive pulmonary disease (COPD) pathogenesis remains unclear, but emerging evidence supports a crucial role for inducible bronchus‐associated lymphoid tissue (iBALT) in disease progression. Mechanisms underlying iBALT generation, particularly during chronic CS exposure, remain to be defined. Oxysterol metabolism of cholesterol is crucial to immune cell localization in secondary lymphoid tissue. Here, we demonstrate that oxysterols also critically regulate iBALT generation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 70 publications
4
64
0
1
Order By: Relevance
“…Grafts containing germinal centers, however, have a lower life expectancy, indicating a detrimental role for organized lymphoid follicles (73). Based on this knowledge, we targeted the GPCR EBI2, known to be specifically involved in the organization of B cells inside lymphoid follicles (26,31,74). Importantly, we show that EBI2 is expressed in tertiary lymphoid follicles in human BOS/CLAD.…”
Section: Discussionmentioning
confidence: 94%
“…Grafts containing germinal centers, however, have a lower life expectancy, indicating a detrimental role for organized lymphoid follicles (73). Based on this knowledge, we targeted the GPCR EBI2, known to be specifically involved in the organization of B cells inside lymphoid follicles (26,31,74). Importantly, we show that EBI2 is expressed in tertiary lymphoid follicles in human BOS/CLAD.…”
Section: Discussionmentioning
confidence: 94%
“…Constitutive loss of CLEC2 results in an emphysematous lung phenotype. TLO formation is commonly seen in chronic lung inflammation and is associated with diverse lung diseases in humans (10,36), but whether TLO formation is connected to impaired lymphatic flow, and whether TLOs are a cause or a consequence of lung disease, remains unclear (50,51). The primary formation of TLOs in mice with impaired lymphatic flow led us to ask whether lymphatic impairment might result in lung injury and pathology.…”
Section: Resultsmentioning
confidence: 99%
“…SERPINE2 deficiency was associated with enhanced production of molecules associated with iBALT induction and inflammation, including IL-17, TNF-a, LTa, CXCL13, IFN-g, IL-2, and spontaneous mononuclear cell infiltration, thus boosting formation of iBALT in the lungs (76). Furthermore, using a mouse model of COPD, Jia et al (77) reported that oxysterol metabolism of cholesterol drove iBALT formation and the induction of COPD, similar to what occurs in SLOs. Increased production of a cholesterol-derived metabolite, 7a,25-hydroxy cholesterol, enhanced B cell recruitment into iBALT by interacting with EBV-induced G protein-coupled receptor 2 (EBI2), a G protein-coupled receptor also expressed in lymphocytes and DCs.…”
Section: Friend or Foe: The Protective And Pathological Roles Of Indumentioning
confidence: 88%